COVID Story; Pandemic Was A Universal Challenge - Ayesha Abbasi (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
The SARS-CoV-2 epidemic in recent years has fundamentally altered how people live. SARS-CoV-2 poses a significant hazard to healthcare workers, including doctors, nurses, and paramedics working as front-line personnel in emergency rooms, clinics, wards, and intensive care units in Pakistan due to the country's low middle-income status and restricted healthcare and resource availability.